Utilizing Extension as a Resource in Disaster Response: Florida Extension’s Communication Efforts During the 2017 Hurricane Season - Moses R. Mike; Shelli D. Rampold; Ricky W Telg; Angela B. Lindsey (Journal of Applied Communications, 2020)
Crisis communication plays a significant role for the different audiences for which it is designed. Hurricanes and other disasters have resulted in major economic damage and disruption of social norms for extended periods of time in communities across the globe. In such circumstances, the Cooperative Extension Service is often called to take an active role in preparation, response, and recovery. As part of the local emergency management team, local Extension offices are positioned to provide a research base, relevant information, and faculty. As such, citizens often look to Extension faculty members for emergency resources and expertise. However, standard communication methods can be significantly affected in disaster situations. Further, difficulty to fully anticipate such effects can limit Extension’s ability to communicate with targeted audiences and deliver important information. This descriptive study was conducted to examine Florida Extension offices’ and Extension faculty members’ communication efforts and effectiveness during the 2017 hurricane season. The primary methods used by respondents to communicate with subject matter clientele were email, face to face, and phone; the primary method used to communicate with the public was the internet/web. Respondents felt clientele and the public were only moderately aware of Extension’s efforts during the hurricane season. Future research is needed to investigate Extension faculty members’ choice of communication channels, as well as the ability of these channels to convey information to clientele and the public. Future research should also examine the communication channels and information sources used and preferred by clientele and the public during disasters. Such results should be compared to the findings of this study to inform future practice for communication in disasters.
Keywords: Communication; disaster preparation; disaster response; hurricane; Extension